The influence of rapid growth in broilers on florfenicol pharmacokinetics – allometric modelling of the pharmacokinetic and haemodynamic parameters. Issue 2 (4th March 2017) - Poźniak, B.; Pawłowski, P.; Pasławska, U.; Grabowski, T.; Suszko, A.; Lis, M.; Świtała, M.
ABSTRACT: 1. The aim of this study was to determine if the pharmacokinetics (PK) of florfenicol (FF) undergo age-dependent changes in broilers. Since drug elimination depends on cardiovascular functions, a haemodynamic study was performed in parallel. 2. Broilers of 0.68, 1.27, 2.45 and 5.13 kg were administered FF in a single intravenous dose of 30 mg/kg body weight. Plasma drug concentrations were determined using high-performance liquid chromatography and PK parameters were calculated using a non-compartmental model. Echocardiography was used to measure haemodynamic functions. 3. During growth, the area under the drug concentration-time curve (AUCinf ) increased from 25.7 ± 2.9 to 39.0 ± 8.0 mg h/l. Total body clearance (ClB ) gradually decreased from 1.19 ± 0.14 to 0.80 ± 0.15 l/h/kg. Elimination half-life increased from 0.73 ± 0.08 to 1.07 ± 0.07 h, whereas volume of distribution ( V ss ) remained unchanged. Haemodynamic measurements revealed an increase in cardiac output, from 495 ± 65 to 1303 ± 306 ml/min, in the respective body weight groups. 4. Allometric models for PK and haemodynamic parameters were developed and validated. All models proved to be statistically significant; however, only models for ClB and V ss met stringent validation criteria. Model for ClB was used to calculate an optimal dose for a given age group that provides uniform AUCinf . 5. Age-dependent change in FF kinetics may cause variability in therapeutic response under clinical conditions. A novel approach to the dosing protocol was proposed as a means of optimising therapeutic efficacy.